CO-MORBID DEPRESSION IN ADULTS WITH TYPE 2 DIABETES MELLITUS – A STUDY OF PREVALENCE, SOCIO-DEMOGRAPHIC PROFILE, AND IMPACT ON GLYCEMIC CONTROL - SARMISTHA PRIYADARSHANI,; RUPA PRADHAN, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives are to study the prevalence of depression in established type 2 diabetes mellitus (T2DM) patients and the association of the severity of depression with the level of glycemic control, second, to explore the relationship of co-morbid depression with the sociodemographic variables and diabetic complications, and third, to assess the association of co-morbid depression with the ongoing diabetic treatment regimen. Methods: Data of OPD patients with established diagnosis of T2DM who came for follow-up were collected. A total of 224 patients underwent a clinical and psychiatric evaluation and details were analyzed as per the objectives of the study. Results: The total sample of diabetic patients included 126 (56%) males and 98 (44%) females with the majority seen in the 45–60-year age group. The sociodemographic parameters were assessed and comorbid depression was seen in 83 diabetic patients. Among them, 42 had moderate depression. Females (n=43) outnumbered males and the majority were seen in the 45–60-year age group (n=39). Comorbid depression was most prevalent among unemployed (n=41), urban residents (n=48), joint family (n=49), Hindus (n=73), and people on only insulin treatment regimen (n=33) but all this was statistically insignificant, whereas illiterates (n=45), HbA1C level >7% (n=71), diabetes-related complications (n=50), and diabetic neuropathy being the most common (n=28) among all the complications were seen and this difference was statistically significant. Conclusion: By taking all our research findings, it can be concluded that comorbid depression modifies the course and prognosis of diabetes.